x⁴ - 3x² - 4 = 0
x² = t
t² - 3t - 4 = 0
d = 9 + 16 = 25
x² = -1
нет корней
x² = 4
x₁ = 4
x₂ = -4
ответ: x = 4; -4
1 б(x² - 1)(x² + 4x + 3) = 0
x² + 4x + 3 = 0
d = 16 - 12 = 4
ответ: x = 1; -1; -3
2воспользуемся свойством пропорции:
x² - 4 = 0
x² = 4
x = ±4
ответ: x = 4; -4
2 бвоспользуемся свойством пропорции:
x² - 3x - 10 = 0
d = 9 + 40 = 49
ответ: x = -2; 5
2 вответ: x = 1; -4
3(x² + 2x)² + 13(x² + 2x) + 12 = 0
x² + 2x = t
t² + 13t + 12 = 0
d = 169 - 48 = 121
x² + 2x = -12
x² + 2x + 12 = 0
d = 4 - 48 = -44
нет корней
x² + 2x = -1
x² + 2x + 1 = 0
d = 4 - 4 = 0
ответ: x = -1
прости, с 4-ым не смогу .
D=4+4*8=36
x₁=2-6=-2
2
x₂=2+6=4
2
x₁*x₂=-2*4= -8
ответ: -8
3. 5(х-6)(х+7)<0
(x-6)(x+7)<0
x=6 x=-7
+ - +
-7 6
x∈(-7; 6)
ответ: (-7; 6)
4) {2x+15>0
{7x-14>0
{2x>-15
{7x>14
{x>-7.5
{x>2
-7.5 2
x>2 или х∈(2; +∞)